2010
DOI: 10.4049/jimmunol.1001472
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Deficiency Regulates Th Lineage Commitment and Modulates Autoimmunity

Abstract: Reactive oxygen species are used by the immune system to eliminate infections; however, they may also serve as signaling intermediates to coordinate the efforts of the innate and adaptive immune systems. In this study, we show that by eliminating macrophage and T cell superoxide production through the NADPH oxidase (NOX), T cell polarization was altered. After stimulation with immobilized anti-CD3 and anti-CD28 or priming recall, T cells from NOX-deficient mice exhibited a skewed Th17 phenotype, whereas NOX-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
169
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(185 citation statements)
references
References 66 publications
(81 reference statements)
11
169
2
Order By: Relevance
“…Some investigators have argued for a critical role, in particular in later, effector processes (36)(37)(38), although others have cautioned about possible misinterpretations of findings from Th17 transfer experiments because of the conversion to or expansion of Th1 cells (39,40). In clear contradiction, IL-17-producing cells were found either to inhibit diabetes in NOD mice, as well as in BioBreeding rats, in several experimental contexts (41)(42)(43) or to have no effect (44). These divergent conclusions likely reflect multiple complexities: that different Th subsets may play variable roles according to the particular disease stage; that multiple cell types can produce IL-17; and that Th17 cells produce cytokines other than IL-17.…”
Section: Discussionmentioning
confidence: 91%
“…Some investigators have argued for a critical role, in particular in later, effector processes (36)(37)(38), although others have cautioned about possible misinterpretations of findings from Th17 transfer experiments because of the conversion to or expansion of Th1 cells (39,40). In clear contradiction, IL-17-producing cells were found either to inhibit diabetes in NOD mice, as well as in BioBreeding rats, in several experimental contexts (41)(42)(43) or to have no effect (44). These divergent conclusions likely reflect multiple complexities: that different Th subsets may play variable roles according to the particular disease stage; that multiple cell types can produce IL-17; and that Th17 cells produce cytokines other than IL-17.…”
Section: Discussionmentioning
confidence: 91%
“…A small induction of ROS has been detected earlier in blood granulocytes of BQ.Ncf1 m1J/m1J mice [22], and residual PMA-induced ROS production was also observed in neutrophils and macrophages of NOD.Ncf1 m1J mice [7]. Combined with the observation that the mutant protein is completely defective in activating NOX2, we conclude that the small inducible ROS production is not dependent on p47phox but can be derived from NOX2 activated by other mechanisms or cellular sources other than the NOX2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the detected p47phox protein corresponded to the mRNA splice variant, which lacked 24 nt in the beginning of Exon 8, and this mRNA variant was concluded to be the only one expressed as protein, although at very low levels. A similar low-level expression of p47phox has since been reported in bone marrow macrophages of NOD.Ncf1 m1J mice [7]. NOX2-derived ROS are multifaceted regulators of the immune system [8].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In parallel, using NADPH oxidase deficient NOD mice, Tse et al showed that the lack of NADPH oxidase resulted in protection against T1D. The mechanism involved in this protection was the polarization of T cells to Th17 phenotype instead of Th1 pattern in NOD mice NADPH oxidase deficient, suggesting that Th1 cells are more pathogenic than Th17 cells in promoting T1D [78].…”
Section: A Protective Role Of Th17 Cells/il-17 In Experimental T1d Dementioning
confidence: 99%